Mobile App-Based Lifestyle Coaching Intervention for Patients With Nonalcoholic Fatty Liver Disease: Randomized Controlled Trial - Oh Young Kwon; Mi Kyung Lee; Hye Won Lee; Hyerang Kim; Jae Seung Lee; Yeonsoo Jang (JMIR Publications, 2024)
BackgroundLifestyle modification in patients with nonalcoholic fatty liver disease (NAFLD) is key to improving health outcomes. Mobile health technologies may offer potential effective and efficient health care support to facilitate self-management. ObjectiveThis study aims to develop a lifestyle coaching intervention using a mobile app for patients with NAFLD and evaluate physiological and psychological health outcomes for 6 months. MethodsThis study was a randomized controlled trial. The personalized lifestyle coaching intervention using a mobile app was developed through established guidelines and literature reviews. This intervention consisted of information on NAFLD management, diet and physical activity self-monitoring, and coaching sessions based on patient records and SMS text messages. A total of 102 individuals were enrolled in the study and randomly assigned to the intervention group (n=48) or the control group (n=54). The outcomes were improvements in physiological (weight, liver fat score, aspartate aminotransferase, alanine transferase, and gamma-glutamyl transferase) and clinical outcomes (self-management, NAFLD self-management knowledge, self-efficacy, fatigue, depression, and quality of life). Data were analyzed using descriptive analysis and a linear mixed model to test the effects of the intervention. ResultsAll participants completed the study. The mean age of the participants was 48.9 (SD 13.74) years, 38.2% (39/102) were female participants, and 65.7% (67/102) were married. There were no differences in baseline demographic and clinical data between the intervention and control groups. Changes from baseline to 6 months were significant only within the intervention group for weight (P<.001), liver fat score (P=.01), aspartate aminotransferase (P=.03), alanine transferase (P=.002), gamma-glutamyl transferase (P=.04), self-management (P<.001), fatigue (P=.005), depression (P=.003), and quality of life (P<.001). The differences between the 2 groups for the changes over the 6 months were significant in self-management (P=.004), self-management knowledge (P=.04), fatigue (P=.004), depression (P=.04), and quality of life (P=.01). However, the intervention-by-time interaction was significantly effective only for self-management (P=.006) and fatigue (P=.02). ConclusionsNonpharmacological interventions using a mobile app may be effective in improving the physiological and psychological health outcomes of patients with NAFLD. Trial RegistrationClinical Research Information Service KCT0005549; http://tinyurl.com/y2zb6usy